Perception of Resident Doctors towards Food Labelling: A Descriptive Study from India - Shalini Singh; Ankit Raj; Monika Rathore (Preventive Medicine: Research & Reviews, 2024)
Background: Perception of front-of-package label (FOPL) amongst doctors is crucial to sensitise patients towards healthy eating choices using FOPL. This study was conducted to assess knowledge, attitude and practices (KAP) of FOPL amongst resident doctors. Methods: A descriptive study was carried out on 100 resident doctors at Sawai Man Singh Medical College during the period of September–November 2023. KAP regarding FOPL were assessed using validated questionnaire, scored and categorised as per Bloom’s criteria. Results: The study showed a mean KAP score of 8.17 ± 1.95 for the participants, out of maximum score of 15. Participants scored highest in the knowledge (4.07 ± 1.08) and lowest in the practice section (0.90 ± 1.16). Although 99% of respondents were aware about some labelling on packaged food items, only 23% of respondents were aware about FOPL. Majority of the respondents rarely or never read nutrition labels (87%) or compared nutritional content of two similar items before purchasing (89%). Sixty-two per cent of respondents considered nutrition labelling as a guarantee of food safety. ‘Multiple Traffic Light’ was the most preferred FOPL design (43%), followed by ‘Health Star Rating’ (21%). Conclusion: There is low awareness of FOPL and a knowledge-behaviour gap amongst the residents. This gap needs to be addressed to ensure better patient counselling for healthy eating choices.